THE INFLUENCE OF TANGRAM MEDIA ON STUDENTS' INTEREST TO IMPROVE THE STUDENTS’ ENTHUSIASTISM IN LEARNING - Eka Nur Kholisah (Universitas PGRI Palembang, 2023)
This research was motivated by students' low interest in learning due to a lack of enthusiasm for learning in mathematics subjects, so that students were not interested in learning, liked to talk to friends, and did not pay attention to the teacher when teaching during the learning process. And also by using learning media that does not involve students in the teaching and learning process so that students are less enthusiastic in learning, not motivated because they are not involved in learning and causes students to be inactive during learning. This research aims to determine the influence of tangram media on students' interest in learning flat shape material in class IV at SD Negeri 30 Palembang. This research was carried out at SD Negeri 30 Palembang which is located on Jl. Freshwater River, 29 Ilir, Kec. Ilir Barat II, Palembang City, South Sumatra. This research is a type of experimental research, namely the True Experimental Design type. The population and sample in this research were fourth grade students at SD Negeri 30 Palembang, totaling 32 students in the control class and 32 students in the experimental class. Data collection techniques in this research are observation, questionnaires and documentation. Data analysis techniques in this research include Normality Test, Homogeneity Test, Hypothesis Test. The results of this research are hypothesis testing showing that t count ≥ t table or 6.938 ≥ 0.349, so it can be concluded that H0 is rejected and Ha is accepted. This means that there is an influence of tangram media on students' interest in learning flat shape material in class IV at SD Negeri 30 Palembang.